Keystone at Horniman Circle - Ghosh, Ayan (2023)
The keystones at Horniman Circle are iconic for their portraits of bearded old men. Each keystone has a unique face and set expression, though they all have some common characteristics, like long beards, flowing locks of hair, deep-set eyes, and a floral ribbon tied in a knot on the head.